SINTESIS, UJI AKTIVITAS ANTIOKSIDAN DAN ANTIKANKER SENYAWA 3′,4′-DIMETHOXY FLAVONOL - Muhamad Rokim (Indonesian Journal of Pure and Applied Chemistry, 2019)
3′,4′-dimethoxy flavonol have been synthesized from 3,4-dimethoxy-2’-hydroxychalcon under basic condition (KOH). The structures of all compounds were characterized based on the interpretation of HPLC chromatorgrams and spectroscopic data including UV, FTIR, NMR and HRMS. Antioxidant activity was evaluated using the DPPH assay and anticancer activity was evaluated using the MTS assay which showed that the 3′,4′-dimethoxy flavonol was active as antioxidants and weak anticancer activity.